Rough water performance of lightweight high-speed craft. (August 2014) - Garme, Karl; Rosén, Anders; Stenius, Ivan; Kuttenkeuler, Jakob
Previous studies have shown how the use of composite materials and application of sophisticated design methods can give significantly lighter high-speed craft structures than what is normally achieved for traditional aluminium designs. A reduction in structural mass and a corresponding reduction in displacement improve the craft calm water performance but can be unfavourable regarding the rough water performance. Here, the rough water performance of two versions of a fast patrol vessel, one in aluminium and the other in carbon fibre sandwich, is studied with simplified semi-empirical methods and more advanced non-linear time domain simulations. In speeds up to 30 knots, the rough water performance of the two craft versions is found to be practically equal. At higher speeds, the lighter composite craft experiences higher vertical accelerations than the heavier aluminium craft, which implies less operational availability. Using trim ballast tanks, the rough water performance of the lighter craft is improved, and it is shown that the acceleration levels can be reduced and even lowered relative to the heavier aluminium craft. This means that the calm water advantages of a lighter composite vessel can be utilized with the same ride comfort and operational availability as for a heavier aluminium vessel.